A randomized clinical trial comparing plaque removal efficacy of an oscillating–rotating power toothbrush to a manual toothbrush by multiple examiners. Issue 4 (6th May 2016) - Kurtz, B; Reise, M; Klukowska, M; Grender, JM; Timm, H; Sigusch, BW
Abstract: Objective: To determine whether multiple examiners can demonstrate consistent plaque removal advantages for an oscillating–rotating power toothbrush versus a manual toothbrush. Methods: This was a replicate‐use, single brushing, examiner‐blind, randomized, two‐treatment, four‐period crossover clinical trial involving four examiners. Subjects were randomized to one of four treatment sequences involving two toothbrushes: an oscillating–rotating power toothbrush or a manual toothbrush. At each of the four visits, subjects arrived having abstained from oral hygiene for 24 h prior, and brushed with their assigned toothbrush and a marketed fluoride dentifrice under supervision unaided by a mirror. Plaque was assessed by each examiner using the Turesky‐Modified Quigley–Hein Plaque Index at each study period before and after brushing. Data was analysed separately for each examiner using the analysis of covariance for crossover design. Results: Ninety‐five subjects between the ages of 18 and 70 met the entrance criteria and were enrolled in the study. Eighty‐seven subjects completed all four periods of the study. Both brushes delivered a significant plaque reduction when compared to baseline. Significant treatment differences were observed for all four examiners – ranging from 0.10 to 0.16 – in favor of the oscillating–rotating brush ( P < 0.001). There were no adverse events reported or observed for either brush. Conclusions: All four examiners demonstrated the power toothbrush removed significantly more plaque after a single brushing than the standard manual toothbrush. Both brushes were well tolerated.